Study on the calculational framework development of the advanced numerical reactor neutronics code SHARK - Hongbo, Zhang; Wenbo, Zhao; Chen, Zhao; Bo, Wang; Zhang, Chen; Xingjie, Peng; Qing, Li; Yingrui, Yu; Zhaohu, Gong; Wei, Zeng (Frontiers in Energy Research, 2023)
The SHARK program (Simulation-based High-fidelity Advanced Reactor physics Kit) is a high-fidelity heterogeneous neutronics code for the numerical reactor system being developed at the Nuclear Power Institute of China (NPIC). The program uses a Constructive Solid Geometry (CSG) framework to model various complex geometries. To enhance the flexibility and robustness during continuous development process, SHARK program attempts to support a rich set of methods, tools and library options within a unified general framework as a “toolkit”. For the multi-core clustered supercomputer architectures that are commonly used today, the SHARK program adopts a hybrid parallel strategy of MPI and OpenMP to achieve complementary advantages between them. In addition, the framework of SHARK program is designed with a true object-oriented manner. Through reasonable abstraction, inheritance and encapsulation, the maintainability and extensibility of the code are improved, and long-term team development is facilitated. Up to now, key modules for cross-section generation, heterogeneous transport calculation and microscopic depletion have been developed under the general frameworks. The main features of SHARK’s “resonance-transport-depletion” coupling system are elaborated in this paper, and some verification and validation (V&V) results in the current phase are presented and discussed.